Identifying motivating factors among college students that influence repeat participation among special event volunteers: the moderating role of class standing. Issue 2 (23rd February 2021) - Beckman, Eric; Pan, Tianyu; Kitterlin, Miranda; Cain, Lisa
Abstract : Purpose: The purpose of this study is to identify the motivating factors that influence repeat participation among university student volunteers at a world-renowned food festival. The direct and indirection relationship (through attitude toward volunteering) was tested. Additionally, the moderating role of class standing between student volunteers' motivations, attitudes and repeat volunteer intention was assessed. Design/methodology/approach: Researchers applied a quantitative methodology to data collected after the festival volunteering experience. The research team collected 205 useable surveys from university student volunteers at the Food Network and Cooking Channel South Beach Wine and Food Festival (SOBEWFF®). Structural equation modeling was used to test the relationships among volunteer motivations, attitude toward volunteering and intention to continue volunteering. Lastly, a multiple-group analysis was applied to test the moderating role of class standing. Findings: The results showed the motivating factors purposive, personal enrichment and family traditions were significant in predicting attitude toward volunteering. These motivations did not significantly affect intention to continue volunteering; thus researchers found only an indirect relationship (through attitude toward volunteering) between volunteering motivations and intention to continue volunteering. Additionally, a positive attitude toward volunteering resulted in an intention to continue volunteering. Lastly, testing the moderating role of class standing revealed significant results on three pathways, indicating that students are motivated to volunteer differently based upon class standing (freshman through junior vs. senior, graduate). Research limitations/implications: The data were collected prior to COVID-19, and the ways in which COVID-19 has impacted the events industry and the scape of future events are yet to be determined. Practical implications: Festival organizers and managers should appeal to different motivations of potential student volunteers depending on their class standing. For example, results of the moderator "class standing" indicated that the relationship between personal enrichment motivation and attitude toward volunteering was strongest and significant among freshmen, sophomores and juniors, but insignificant among seniors and graduate students. Thus, freshmen through juniors are more highly motivated to obtain practical experiences, and this motivation results in a positive attitude toward volunteering. Originality/value: This study tests the moderating role of class standing to help predict intention to continue volunteering at a special event. The research is further unique by extending an understanding of the validity and reliability of the special events volunteer motivations scale.